THE COURSE OF IRON DEFICIENCY ANEMIA IN CHILDREN - Hamidova Feruza Karimova (Scholars Digest Publishing, 2023)
Iron deficiency anemia (WAIT) is an acquired disease from the group of deficiency anemia; accompanied by microcytic, hypochromic, normoregenerative anemia; clinically manifested by a combination of sideropenic and anemic syndromes. IDA includes the following nosological forms having the corresponding codes of the International Statistical Classification of Diseases and Health-Related Problems, 10th revision (ICD-10): IDA (D50), chronic posthemorrhagic anemia (D50.0), anemia complicating pregnancy, childbirth and the postpartum period (O99.0), currents, iron deficiency anemia, children
Keywords: anemia, children, treatment. Diagnostics.